2005
DOI: 10.1164/rccm.200409-1242oc
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Noninvasive Measurements of Airway Inflammation in Steroid Reduction in Children

Abstract: The use of noninvasive methods of monitoring airway inflammation, such as exhaled nitric oxide (eNO) and induced sputum, has been shown to improve asthma monitoring and optimize treatment in adult patients with asthma. There is a lack of comparable data in children. Forty children with stable asthma eligible for inhaled steroid reduction were reviewed every 8 weeks, and their inhaled steroid dose halved if clinically indicated. eNO, sputum induction combined with bronchial hyperreactivity testing, and exhaled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
216
2
16

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(246 citation statements)
references
References 28 publications
12
216
2
16
Order By: Relevance
“…50 Emerging information indicates that assessment of within-individual changes in FeNO may be a more accurate method for In general for children, elevated eosinophil counts in sputum may be more sensitive for predicting asthma exacerbations or loss of asthma control after steroid reduction than elevated FeNO. 49 This is because high FeNO is not always pathological, whereas induced sputum eosinophil counts >1% is abnormal. An induced sputum test with no eosinophils is very useful in predicting that exacerbations will not occur.…”
Section: ) Measuring Feno To Guide Asthma Management and Monitor Astmentioning
confidence: 99%
“…50 Emerging information indicates that assessment of within-individual changes in FeNO may be a more accurate method for In general for children, elevated eosinophil counts in sputum may be more sensitive for predicting asthma exacerbations or loss of asthma control after steroid reduction than elevated FeNO. 49 This is because high FeNO is not always pathological, whereas induced sputum eosinophil counts >1% is abnormal. An induced sputum test with no eosinophils is very useful in predicting that exacerbations will not occur.…”
Section: ) Measuring Feno To Guide Asthma Management and Monitor Astmentioning
confidence: 99%
“…Cette valeur-seuil provient d'un certain nombre d'études investiguant le rôle de la mesure du FE NO [22,[79][80][81][82] . Chez ces patients se présentant avec des symptômes respiratoires non spécifiques, un taux bas de FE NO suggère des diagnostics alternatifs qui ne seront pas amé-liorés par un traitement par corticostéroïdes inhalés (Tableau 3).…”
Section: Intérêt Pour L'identification Des Phénotypes Inflammatoires unclassified
“…En effet, une diminution de 40 % du taux de FE NO chez un patient permettait de prédire une réduction du score d'ACQ et donc une amélioration du contrôle de l'asthme avec une valeur prédictive positive de 83 % et une valeur prédictive négative de 79 % [95] . En ce qui concerne les seuils permettant de prédire une perte de contrôle de l'asthme, Zacharasiewicz a rapporté qu'un taux de FE NO supérieur à 22 ppb chez des enfants traités par stéroïdes inhalés est associé à un risque six fois supérieur de perte de contrôle de l'asthme pendant la réduction du traitement par corticosté-roïdes [82] . Une autre étude, toujours chez l'enfant, a trouvé qu'un taux de FE NO supérieur à 49 ppb un mois après l'arrêt du traitement par corticostéroïdes inhalés présentait une sensibilité et une spécificité optimale pour la prédiction d'une perte de contrôle [96] .…”
Section: Contrôle Et Sévérité De L'asthmeunclassified
“…26 Although FeNO and eosinophilic inflammation do not relate closely to markers of asthma control (i.e. symptoms and disordered airway function), they do relate to asthma exacerbations, 27,28 implying that assessment of inflammation provides information about asthma not available through other means. A dose-titration adult study reported that adjustments of ICS dose informed by FeNO estimation allowed a reduction in ICS dose without loss of control, 29 and a paediatric study reported improved bronchial hyperresponsiveness without any difference in the overall ICS load received.…”
Section: Introductionmentioning
confidence: 99%